2006
DOI: 10.1088/0022-3727/39/14/010
|View full text |Cite
|
Sign up to set email alerts
|

Studies of swift heavy ion induced colour centres in LIF thin films deposited on silica substrates

Abstract: Swift heavy ion induced colour centres in polycrystalline LiF thin films deposited on silica substrate were studied. LiF thin films of 200 nm thickness, deposited by the electron beam evaporation method, and silica substrates were irradiated with 120 MeV Au9+ ions in the fluence range 5 × 1010–1 × 1013 ions cm−2. Optical absorption, photoluminescence (PL) and glancing angle x-ray diffraction (GAXRD) techniques were used for the characterization of the irradiated films. Optical absorption spectroscopy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Baldacchini et al [12,13] compared CCs formation by extreme ultraviolet radiation, soft X-rays and by electrons in LiF crystals and thick film ($6 mm thickness) and they showed that the main spectroscopic features of the defects in polycrystalline films were same as those observed in crystals, but the formation efficiency of CCs was higher in film, where surface to volume ratio and the film compactness played a major role because of the presence of high density of grain boundaries. At the same time, in our previous reports [16,18], we observed that the grain size in nanometric films also played an important role in defect creation process and influenced the CCs concentration. The SHI irradiation of nano-granular LiF thin films leads to the formation of CCs as well as grain fragmentation simultaneously.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Baldacchini et al [12,13] compared CCs formation by extreme ultraviolet radiation, soft X-rays and by electrons in LiF crystals and thick film ($6 mm thickness) and they showed that the main spectroscopic features of the defects in polycrystalline films were same as those observed in crystals, but the formation efficiency of CCs was higher in film, where surface to volume ratio and the film compactness played a major role because of the presence of high density of grain boundaries. At the same time, in our previous reports [16,18], we observed that the grain size in nanometric films also played an important role in defect creation process and influenced the CCs concentration. The SHI irradiation of nano-granular LiF thin films leads to the formation of CCs as well as grain fragmentation simultaneously.…”
supporting
confidence: 54%
“…PL properties of CCs in LiF crystals [6][7][8][9][10][11][12][13] and films [5,[12][13][14][15][16][17] has been extensively investigated, however, only a few reports are available on PL properties of swift heavy ions (SHI)-induced CCs in nanometer sized LiF thin films [16][17][18]. In case of thin film, the PL intensity strongly depends on growth and irradiation parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that SHI beam induces radiative defects in insulators and semiconductors and PL-intensity is sensitive to damages created by SHI beam [17]. Photoluminescence studies of unirradiated and irradiated TiO 2 thin films are carried out using spectrofluorimeter SPEX-Fluorolog.…”
Section: The Pl-spectroscopymentioning
confidence: 99%
“…Increase in luminescence intensity observed after irradiation may be due to SHI-induced defects in TiO 2 which act as radiative recombination centers [17]. Oxygen vacancies have been considered as the most common defects and usually act as radiative centers in luminescence processes [21].…”
Section: The Pl-spectroscopymentioning
confidence: 99%